Business Process Modelling and its Use Within an Elite Training Environment - Justham, L; Slawson, S; West, A.; Conway, P.; Caine, M.; Harrison, R. (The Engineering of sport 7, Volume 1, 2008)
In this paper the Computer Integrated Manufacture Open System Architecture (CIMOSA) business process modelling approach has been used in the development of a module to support coaches and athletes in swimming. A review of existing modelling approaches was carried out and it was decided that the CIMOSA approach was the most appropriate for this application as it is a stand alone, integrated technique which can be used in both system planning and analysis.